Neurofilament, but not Alzheimer disease biomarkers in the acute phase correlate with cognitive performance after cardiac arrest - Johannes Lorentzson; Gisela Lilja; Erik Blennow Nordström; Kaj Blennow; Henrik Zetterberg; Christian Hassager; Matt P. Wise; Andrea L. Benedet; Tommaso Pellis; Hans Friberg; Nicholas Ashton; Marion Moseby Knappe (Resuscitation Plus, 2025)
Background: Biomarkers serve as a quantitative measure of brain injury and may predict cognitive outcome after cardiac arrest. This study investigates the association and predictive accuracy of acute changes in Alzheimer disease-associated biomarkers to cognitive outcome in cardiac arrest survivors. Methods: Retrospective study of the Target Temperature Management after Out-of-Hospital cardiac arrest trial. Serum from adult cardiac arrest survivors was sampled prospectively at 24, 48, and 72 h post-arrest and analyzed for peak-levels of Alzheimer disease markers (p-tau181, total tau, amyloid β [Aβ40 and Aβ42]), and the neurodegenerative biomarker neurofilament light (NfL). Cognitive outcome was evaluated blinded from biomarker results using four performance-based assessments at 6 months post-arrest. Spearman correlations were calculated. Area Under the Receiver Operating Characteristics curves (AUC) were calculated for biomarkers discriminatory ability for binary results of cognitive performance. Results: 206/342 (60 %) survivors from participating sites were included. Median was age 62 (IQR 53–69), 86 % male, 15 (7 %) had Mini-Mental State Examination (MMSE) scores < 24. Alzheimer disease biomarkers exhibited at best small correlations to cognitive outcomes (rho = −0.22 to 0.18). The correlation between outcome instruments and NfL was rho = −0.32 to −0.20 (p < 0.01). Discriminatory ability of cognitive impairment for acute changes in Alzheimer disease biomarkers was AUC 0.44–0.68 (95 % CI 0.29–0.82), and AUC 0.66–0.86 (95 % CI 0.59–0.95) for NfL. Conclusion: In contrast to tau- and amyloid-related biomarkers, NfL could be more useful for predicting cognitive function in cardiac arrest survivors. Low participation by survivors with severe brain injury may have influenced results.